Music, body, and desire in medieval culture: Hildegard of Bingen to Chaucer - Holsinger, Bruce, W. (California Stanford university press, 2001)
Ranging chronologically from the twelfth to the fifteenth centuries and thematically from Latin to vernacular literary modes, this book challenges standard assumptions about the musical cultures and philosophies of the European Middle Ages. Engaging a wide range of premodern texts and contexts, from the musicality of sodomy in twelfth-century polyphony to Chaucers representation of pedagogical violence in the Prioresss Tale, from early Christian writings on the music of the body to the plainchant and poetry of Hildegard of Bingen, the author argues that medieval music was quintessentially a practice of the flesh.The book reveals a sonorous landscape of flesh and bone, pleasure and pain, a medieval world in which erotic desire, sexual practice, torture, flagellation, and even death itself resonated with musical significance and meaning. In its insistence on music as an integral part of the material cultures of the Middle Ages, the book presents a revisionist account of an important aspect of premodern European civilization that will be of compelling interest to historians of literature, music, religion, and sexuality, as well as scholars of cultural, gender, and queer studies.About the authorBruce W. Holsinger is Assistant Professor of English at the University of Colorado.